2018
DOI: 10.1111/ijd.14038
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic patterns of filiform papillae of the tongue in patients with and without connective tissue autoimmune diseases

Abstract: We have noted alterations in filiform papillae in CTADs, which emphasizes the importance of a detailed intraoral exploration and the macroscopic and dermoscopic evaluation of the dorsum of the tongue, specifically the filiform papillae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Data from the literature also suggest that (video)dermoscopy may be useful in the evaluation of filiform papillae of the tongue in connective tissue diseases (CTD) [13]; however, in our study, we did not perform videodermoscopy in this location.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Data from the literature also suggest that (video)dermoscopy may be useful in the evaluation of filiform papillae of the tongue in connective tissue diseases (CTD) [13]; however, in our study, we did not perform videodermoscopy in this location.…”
Section: Discussionmentioning
confidence: 84%
“…The (video)dermoscopic features of skin symptoms in the course of DM have not been extensively studied so far [7][8][9][10][11][12][13][14][15]. Data from the literature point at potential application of (video)dermoscopy in the assessment of nailfolds (capillaroscopy) [7][8][9][10], scalp (trichoscopy) [11,12], filiform papillae of the tongue [13], hand lesions [14], and cutaneous changes in erythrodermic DM [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7]11 Dermoscopy has also been utilized for the visualization of filiform papillae of the tongue in connective tissue diseases. 9 Trichoscopic features of DM have also been reported in a few papers. 10,12,13 Jasso-Olivares et al analysed scalp dermoscopy in 31 patients with DM and observed the presence of enlarged tortuous capillaries (71.4%), peripilar casts (57.1%), tufting, interfollicular scales (50%) and, in a smaller percentage of cases, bushy capillaries, inter-and perifollicular pigmentation and vascular lake-like structures.…”
Section: Discussionmentioning
confidence: 88%
“…There are scarce data in the literature on the application of (video)dermoscopy in DM. [5][6][7][8][9][10][11][12][13] So far, dermoscopy has been predominantly used for the assessment of nail fold capillaries and proved to be a reliable tool to detect dilated capillaries, 'bushy' capillaries, nail fold bleedings and avascular areas. [5][6][7]11 Dermoscopy has also been utilized for the visualization of filiform papillae of the tongue in connective tissue diseases.…”
Section: Discussionmentioning
confidence: 99%